1999
DOI: 10.1086/314708
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Changes in Hepatitis C Virus Genotypes among Multitransfused Persons with Hemophilia

Abstract: The purpose of this study was to determine hepatitis C virus (HCV) genotypes and their relationship to HCV RNA levels over time in a cohort of multitransfused hemophiliacs. Following reverse transcription and polymerase chain reaction amplification of HCV RNA, the product DNAs were genotyped by using the line probe assay. HCV RNA was quantified by the branched-chain DNA assay. Genotyping was done on 109 serum samples from 32 subjects. Genotype 3a had the highest prevalence (41%), followed by genotypes 1a (31%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
71
1
4

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(81 citation statements)
references
References 46 publications
(61 reference statements)
5
71
1
4
Order By: Relevance
“…Some groups investigated the dynamics of the change in genotype in more detail, analyzing series of samples from different time points. There was no obvious trend towards replacement with any particular variant Eyster et al, 1999). Regardless the origin of the genotype shift (reinfection or reactivation), it could be revealing the presence of a mixed infection in the hemophilic patient.…”
Section: Hcv Mixed Genotype Infections In Hemophilic Patientsmentioning
confidence: 87%
See 3 more Smart Citations
“…Some groups investigated the dynamics of the change in genotype in more detail, analyzing series of samples from different time points. There was no obvious trend towards replacement with any particular variant Eyster et al, 1999). Regardless the origin of the genotype shift (reinfection or reactivation), it could be revealing the presence of a mixed infection in the hemophilic patient.…”
Section: Hcv Mixed Genotype Infections In Hemophilic Patientsmentioning
confidence: 87%
“…However, selective transmission of HCV isolates during experimental chimpanzee infections and among humans exposed to commercially prepared factor VIII concentrate (lot DO56) containing multiple HCV species has also been suggested (Nainan et al, 2006). The analysis of genotype distribution showed that several HCV genotypes might be circulating simultaneously in adults with hemophilia who received clotting factor concentrates before 1985 Eyster et al, 1999;Schröter et al, 2003). Genotyping studies of multitransfused haemophiliacs suggested that the frequency of HCV mixed infection is high in this group but dissimilar rates of mixed infections were reported by different groups (Table 1).…”
Section: Hcv Mixed Genotype Infections In Hemophilic Patientsmentioning
confidence: 99%
See 2 more Smart Citations
“…63 Nevertheless, chronically infected humans remain susceptible to new infection. Eyster et al 64 documented a common change of infecting HCV genotypes over time in high-risk patients with hemophilia and recently Herring et al 65 identified superinfection in 20% of active IDUs over a period of 12 months. Similarly, it was shown that chronically infected patients can be superinfected with new HCV strains in the setting of blood transfusion, where HCV-positive patients were exposed to HCV-positive blood, 66 and in the setting of liver transplantation, where patients with HCV-related liver disease receive organs from HCV-infected donors.…”
Section: Discussionmentioning
confidence: 99%